Sickle cell anaemia and the NBT test - Walters, Thomas R. (1974)
Patients with sickle cell anaemia have an increased susceptibility to bacterial infections Previous reports of false-negative nitro blue tetrazolium (NBT) tests in the presence of bacteria infection and of a faulty phagocytic response following stimulation in vitro have suggested the possibility of polymorphonuclear dysfunction in certain patients with sickle cell anaemia. In the present study an unstimulated, histochemical NBT technique was used to evaluate the test in patients with sickle cell anaemia. There was a significant difference between the results in the group of patients with infection (mean NBT-positive cells 42·7%) compared to those without infection (mean 9·4%). There was no significant correlation between the total white blood cell count, absolute number of polymorphonuclear cells, and infectious complications. These findings indicate an appropriate polymorphonuclear cell response, as evaluated by the NBT test, in patients with sickle cell anaemia and bacterial infection. The NBT test may be used as an additional parameter in the differentiation of those patients with sickle cell anaemia with bacterial infection.